2020
DOI: 10.1523/jneurosci.1633-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Cholinergic Signaling Modulates Sound-Evoked Responses of the Medial Nucleus of the Trapezoid Body

Abstract: The medial nucleus of trapezoid body (MNTB) is a major source of inhibition in auditory brainstem circuitry. The MNTB projects well-timed inhibitory output to principal sound-localization nuclei in the superior olive (SOC) as well as other computationally important centers. Acoustic information is conveyed to MNTB neurons through a single calyx of Held excitatory synapse arising from the cochlear nucleus. The encoding efficacy of this large synapse depends on its activity rate, which is primarily determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…Cholinergic neurons in the PMT project broadly to CN, IC, and auditory thalamus (Schofield et al, 2011). We previously showed that the MNTB receives input from cholinergic cells of the SOC and the PMT (Zhang et al, 2021). In that report, we showed a tracer deposit restricted to the MNTB resulted in labeled cholinergic cells in the PMT and SOC.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Cholinergic neurons in the PMT project broadly to CN, IC, and auditory thalamus (Schofield et al, 2011). We previously showed that the MNTB receives input from cholinergic cells of the SOC and the PMT (Zhang et al, 2021). In that report, we showed a tracer deposit restricted to the MNTB resulted in labeled cholinergic cells in the PMT and SOC.…”
Section: Introductionmentioning
confidence: 72%
“…Developmental knock-out of alpha-7 nicotinic receptors suggests that ACh may contribute to temporal processing in the superior paraolivary nucleus (Felix et al, 2019). We have shown previously that, in the MNTB, ACh affects suprathreshold response magnitude, enhances near-threshold level discrimination, and enhances coding for signal in noise (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Growing evidence indicates that cholinergic signaling through nicotinic acetylcholine receptors (nAChRs) critically shapes sound processing in the central auditory system (Goyer et al, 2016;Askew et al, 2017;Felix et al, 2019;Zhang et al, 2021). The inferior colliculus (IC), the midbrain hub of the central auditory system, receives extensive input from cholinergic neurons in the pontomesencephalic tegmentum (PMT; , and expresses several nAChR subunits, including α3, α4, α7, β2, β3, and β4 (Clarke et al, 1985;Wada et al, 1989;Morley & Happe, 2000;Whiteaker et al, 2002;Salas et al, 2003;Gahring et al, 2004;Happe & Morley, 2004;Bieszczad et al, 2012;Sottile et al, 2017).…”
Section: Introductionmentioning
confidence: 99%